Fine Needle Aspiration Cytology of Palpable Head and Neck Masses: A Descriptive Cross-sectional Study - Chalise, Sanat; Hirachand, Suspana; Dhakhwa, Ramesh (Nepalese Medical Journal, 2024)
Introduction: Fine needle aspiration cytology is a quick and safe technique done for the initial diagnosis of head and neck region masses. This study aims to assess the utility of fine needle aspiration cytology in head and neck palpable masses. Materials & Methods: A descriptive cross-sectional study was done in the Pathology Department of Kathmandu Medical College from 1st February 2023 to 31st December 2023. All the patients with palpable head and neck lumps were included in the study. A convenience sampling method was used. The data was entered and analyzed using the Statistical Package for Social Science (SPSS) version 22.0 Results: Among 650 fine needle aspiration cytology done during the study period, 184 were from head and neck lesions (28.30%). The mean age of the patient was 35.4 years with female predominance. The most common site was lymph node 85 (46.19%) followed by thyroid 39 (21.19%). Reactive lymphadenitis was the most common cause of lymphadenopathy seen in 41(22.2%) patients and colloid goitre was the most common cause of thyroid swelling seen in 26(14.13%) patients. Conclusions: Fine needle aspiration cytology is a useful and reliable technique for the diagnosis of head and neck mass. It helps to avoid unnecessary surgeries and is recommended and guides the clinician in general clinical management.